2015
DOI: 10.1016/s2215-0366(14)00050-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of a staff training intervention in mental health inpatient rehabilitation units designed to increase patients' engagement in activities (the Rehabilitation Effectiveness for Activities for Life [REAL] study): single-blind, cluster-randomised controlled trial

Abstract: National Institute for Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…The results showed that the implementation had positive outcomes for the participants, in terms of reduced stress, retained social functioning, and increased understanding (Jönsson et al, 2011). Killaspy et al (2015) argue that more research is needed to increase the understanding of complexities regarding the implementation of new working models in the psychiatric healthcare contexts. Willman, Stoltz, and Bahtsevani (2011) emphasize the importance of evidence-based practices as well as evaluations within the healthcare sector.…”
Section: Introductionmentioning
confidence: 93%
“…The results showed that the implementation had positive outcomes for the participants, in terms of reduced stress, retained social functioning, and increased understanding (Jönsson et al, 2011). Killaspy et al (2015) argue that more research is needed to increase the understanding of complexities regarding the implementation of new working models in the psychiatric healthcare contexts. Willman, Stoltz, and Bahtsevani (2011) emphasize the importance of evidence-based practices as well as evaluations within the healthcare sector.…”
Section: Introductionmentioning
confidence: 93%
“…78 The main results of the trial and its associated health economic components have been published. 33 The results of the associated qualitative component have also been published. 34 A further paper describing the specific role of the OTs as 'agents of change' during the intervention has been published.…”
Section: Unitmentioning
confidence: 99%
“…33 The qualitative component of phase 3 of the REAL study included focus groups with staff at the intervention units. These revealed that the increased staff skills and changes in practice that were facilitated in units by the GetREAL teams during the enabling stage of the intervention were not sustained during the reinforcing stage (once the GetREAL teams had left the units).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the overall picture of a changing mental health care sector we need highquality efficacy research using randomised controlled trials such as those so brilliantly performed in the UK on the one hand (Burns et al 2013;Killaspy et al 2015) because that type of research can guide us and provide the building blocks in moving forward in intervention research. However, we also need large-scale social, political and economic science studies of complex health care systems and of how they achieve reform and innovation in 'real world' settings.…”
Section: Guidelines and Guideline Implementationmentioning
confidence: 99%